Gender and Sexuality in the Pastoral Encounter. Issue 3 (September 2014) - Grosch-Miller, Carla A.; Ferguson, Sharon; Callaghan, Brendan
<x content-type="archive" xml:space="preserve">Abstract</x> At the 'Embodied Ministry: Gender, Sexuality and Formation' conference at which the articles in this special issue were delivered, three people in active ministry in different denominations — United Reformed Church, Metropolitan Community Church and Roman Catholic — were invited to take part in a panel discussion on gender and sexuality in the pastoral encounter. Their remarks were originally delivered in this conversational context. Martin Pendergast chaired this panel discussion.